CONSERVATIVE CULTIVATION TECHNOLOGIES – A NEW CHALLENGE FOR THE AGRICULTURE OF THE REPUBLIC OF MOLDOVA - Anatolie IGNAT; Victor MOROZ (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development, 2014)
The agriculture of the Republic of Moldova is particularly prone to natural risks, especially droughts. The purposeof this paper is to present the state of sustainable development of the agricultural sector and opportunities forimplementation of the innovative land cultivation technologies. There are a number of socio-economic constraintsfor increasing the productivity in the traditional agricultural systems. In order to meet the growing competition onthe regional markets of agricultural products, modernization of agriculture in the Republic of Moldova is veryimportant. For investigation of the actual state of implementation of the conservative land cultivation technologieswere used specific methods and techniques such as statistical and economic analysis of economic indicators, casestudy approach, semi-structured interviews of agricultural producers. The study is also based on the statisticsreceived from the National Bureau of Statistics and the Ministry of Agriculture and Food Industry of Moldova.Economic analysis confirms that implementation of the No Till technology will reduce essentially the directproduction costs compared to traditional technology. However a more visible effect occurs starting with the 5-6year of the conservative land cultivation technologies’ implementation.